Presenilin1/γ‐secretase protects neurons from glucose deprivation‐induced death by regulating miR‐212 and PEA15. Issue 1 (30th August 2017) - Huang, Qian; Voloudakis, Georgios; Ren, Yimin; Yoon, Yonejung; Zhang, Emily; Kajiwara, Yuji; Shao, Zhiping; Xuan, Zhao; Lebedev, Denis; Georgakopoulos, Anastasios; Robakis, Nikolaos K.
Abstract : Reduced cerebral glucose utilization is found in aged individuals and often is an early sign of neuro‐degeneration. Here, we show that under glucose deprivation (GD) conditions, decreased expression of presenilin 1 (PS1) results in decreased neuronal survival, whereas increased PS1 increases neuronal survival. Inhibition of γ‐secretase also decreases neuronal survival under GD conditions, which suggests the PS1/γ‐secretase system protects neurons from GD‐induced death. We also show that neuronal levels of the survival protein, phosphoprotein enriched in astrocytes at ∼15 kDa (PEA15), and its mRNA are regulated by PS1/γ‐secretase. Furthermore, down‐regulation of PEA15 decreases neuronal survival under reduced glucose conditions, whereas exogenous PEA15 increases neuronal survival even in the absence of PS1, which indicates that PEA15 promotes neuronal survival under GD conditions. The absence or reduction of PS1, as well as γ‐secretase inhibitors, increases neuronal miR‐212, which targets PEA15 mRNA. PS1/γ‐secretase activates the transcription factor, cAMP response element‐binding protein, regulating miR‐212, which targets PEA15 mRNA. Taken together, our data show that under conditions of reduced glucose, the PS1/γ‐secretase system decreases neuronal losses by suppressing miR‐212 and increasing its target survival factor, PEA15. These observations have implications for mechanisms of neuronal death under conditions of reduced glucose and may provide targets for intervention in neurodegenerative disorders.—Huang, Q., Voloudakis, G., Ren, Y., Yoon, Y., Zhang, E., Kajiwara, Y., Shao, Z., Xuan, Z., Lebedev, D., Georgakopoulos, A., Robakis, N. K. Presenilin1/γ‐secretase protects neurons from glucose deprivation‐induced death by regulating miR‐212 and PEA15. FASEB J. 32, 243‐253 (2018). www.fasebj.org